2013
DOI: 10.1093/infdis/jit006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Telomerase Activity by Human Immunodeficiency Virus (HIV) Nucleos(t)ide Reverse Transcriptase Inhibitors: A Potential Factor Contributing to HIV-Associated Accelerated Aging

Abstract: NRTIs and, specifically tenofovir at therapeutic concentrations, inhibit telomerase activity leading to accelerated shortening of TL in activated PBMCs. The relationship between NRTI, reduced telomerase activity, and accelerated aging requires further investigation in HIV-infected individuals on cART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 47 publications
1
94
3
1
Order By: Relevance
“…In the early times of HIV epidemic, NRTIs, including azidothymidine (AZT), didanosine (ddI), and abacavir (ABC) [156-160] were proven to be able to reduce telomerase activity and TL in vitro. More recently, tenofovir (TDF), lamivudine (3TC), and emtricitabine (FTC) have also been found to diminish telomerase activity and TL in vitro [161]. Given the key role of telomerase in the ageing process [162], it has been hypothesized that telomerase inhibition, and possibly NRTI-associated mitochondrial damage, could participate in the premature ageing observed in ART-treated patients.…”
Section: Effect Of Art On Telomerase Activity Of T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early times of HIV epidemic, NRTIs, including azidothymidine (AZT), didanosine (ddI), and abacavir (ABC) [156-160] were proven to be able to reduce telomerase activity and TL in vitro. More recently, tenofovir (TDF), lamivudine (3TC), and emtricitabine (FTC) have also been found to diminish telomerase activity and TL in vitro [161]. Given the key role of telomerase in the ageing process [162], it has been hypothesized that telomerase inhibition, and possibly NRTI-associated mitochondrial damage, could participate in the premature ageing observed in ART-treated patients.…”
Section: Effect Of Art On Telomerase Activity Of T Cellsmentioning
confidence: 99%
“…In the study by Leeansyah et al [165], TL and telomerase activity was analysed in total PBMCs, because the authors hypothesized that if NRTI inhibits telomerase activity, this should occur not only in CD4+ T cells, but in all peripheral blood cells expressing telomerase [161]. The authors detected a significant reduction of telomerase activity (but not of TL) in patients on NRTI-containing therapy, and suggested that the lack of significant shortening of TL in total PBMCs could be ascribed to the divergent changes in TL that have been described for CD4+ and CD8+ T cells.…”
Section: Effect Of Art On Telomerase Activity Of T Cellsmentioning
confidence: 99%
“…15,17 Moreover, telomerase activity could be also compromised by HIV-1 treatment because this enzyme shares homology with one of the main cART targets, the nucleoside reverse transcriptase. 19 In fact, nucleoside reverse transcriptase inhibitors (NRTI) have been shown to inhibit telomerase activity both in vitro and ex vivo [20][21][22] and to shorten TL. [22][23][24] Oxidative reactions are also important factors underlying the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that data from diverse experiments suggest alternatives to the OS theory of aging and have produced results implicating other causal factors for changes in aging processes, such as a lowering of body temperature and associated hypometabolic state, telomerase shortening and alterations in gene expression [78,79]. These factors have been associated with an increased production of prooxidants and induction of OS.…”
Section: Integrative Analysismentioning
confidence: 99%
“…TERT activity is vital to telomerase functions and because of the key role of telomerase in aging theories, it was hypothesized that this inhibition could contribute to the premature aging in HIV/AIDS, and help promote the looming epidemic of premature aging in that population [59,78].…”
Section: Integrative Analysismentioning
confidence: 99%